1956-1964. Giosetta Fioroni meets America in Rome and Paris. The evolution of her figurative language from the "Informale" to the Argenti (L'uomo nero. Materiali per una storia delle arti della modernità, 2023)
At the end of 1957, Giosetta Fioroni left Italy, with the need to find her dimension within the contemporary artistic panorama. Before 1963 she lived between Paris and Rome and during this period she experienced the multiform stimuli of the French cultural milieu, where there were still the echoes of the European avant-gardes. Meanwhile, despite the precarious equilibrium of the Cold War, she maintained contact with her hometown, which attracted several American artists, critics and collectors.  This research aims to demonstrate how Giosetta Fioroni’s intermittent French stay, together with the geographical and cultural distance from her educational environment, allowed her to elaborate a new figurative lexicon and unhinge the previous compositional habits of the Italian Informale. Starting from 1958, Fioroni’s disegni and carte anticipated some pictorial and technical elements that would later distinguish the Argenti.For the first time, it was analytically investigated, through the reconstruction of her exhibitions and her international networks, the central role of some figures in the human and professional growth of Giosetta Fioroni, starting from the découvreurs de talents of the galleries pilotes Facchetti and Breteau to the collector Henry Fara. Moreover, the identification of Gerard Michel also led to bringing forward the date of her first contact with France to 1956.
Keywords: Giosetta Fioroni; Rome; Paris; New York; Informale; Argenti